PENATALAKSANAAN FISIOTERAPI PADA KONDISI CARPAL TUNNEL SYNDROME (CTS) DEXTRA DENGAN MODALITAS ULTRASOUND (US) DAN TERAPI LATIHAN DI RSUD BENDAN KOTA PEKALONGAN - Nurul Faidah; Andung Maheswara (LPPM Universitas Pekalongan, 2014)
Physiotherapy management in condition of Carpal Tunnel Syndrome (CTS) dextra with ultrasound (USD) and Exercise Therapy modalities. The manufacture of this paper was intended to provide information, knowledge and understanding the condition of Carpal Tunnel Syndrome (CTS) dextra that was characterized by the emphasis which the median nerve as the cause of the problems such as pain, spasm, decreased muscle strength, range of joint motion, and the functional abilities. And the given modalities were ultrasound (USD) and Exercise Therapy. Case study was used in the formulated of this paper. To provide an effective and efficient handling, carried out an inspection method of pain with Verbal Descriptive Scale (VDS), spasm examination by palpation, examination of muscle strength with Manual Muscle Testing (MMT), range of joint motion checked with goneometer and the functional capabilities usingWrist hand disability index. To solve those problems, ultrasound (USD) and Exercise Therapy were used to deal with the patient. After the therapies given for six times, obtained a decrease in pain of the patient, (pain at rest) T1 = 2, T6 = 1 (tenderness) T1 = 3, T6 = 1 (motion pain) T1 = 3, T6 = 1, decrease spasm T1 = 3, T6 = 1, an increase in muscle strength T1 = dorsal flexion 4, palmar flexion3+, ulnar deviation of 4+, radial deviation 4+, into T6 = dorsal flexion 5, palmar flexion 4+, ulnar deviation 5, radial deviation 5, an increase in range of motion of wrist T1 = S = 45-0-55, F = 30-0-20, T6 = S = 55-0- 55, F = 30-0-20, the increase of functional ability T1 = 34 (severe dependence), T6 = 13 (mild dependence). From the results obtained, it can be concluded that the use of ultrasound (USD) and Exercise Therapy modalities could help in reduce the problems that arise in the case of Carpal Tunnel Syndrome (CTS) dextra. Keywords: Carpal Tunnel Syndrome (CTS) dextra, Verbal Descriptive Scale (VDS), Spasm, Manual Muscle Testing (MMT), range of motion, Wrist and Hand Disability Index, Ultrasound, Exercise Therapy.